Public Law's Rationalization of the Legal Architecture of Money: What Might Legal Analysis of Money Become?. Issue 5 (1st October 2016) - Feichtner, Isabel
Abstract : Many of the ills afflicting democratic capitalism have their source in the current legal architecture of money and finance. At the same time the reimagination of institutions of money and finance promise an avenue for reform to democratize the economy and prevent the perpetuation of austerity politics. Such institutional reimagination requires a perspective that recognizes money as an institution linking state and civil society, politics and the economy. Economics in great part eschews such a perspective and perceives of money as a medium of exchange largely independent of government and politics. Legal analysis, by contrast, should be ideally suited for the endeavor to analyse the various ways in which the institutional design of money configures political economy.